The Relationship of Diarrhea in COVID-19 Patients With Transaminitis, Severity, and Mortality - Amanda C Wowor; Supriono Supriono; Bogi Pratomo; Syifa Mustika (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background: Coronavirus disease 2019 (COVID-19) is a pandemic that causes various types of symptoms. Diarrhea is a gastrointestinal symptom that is hypothesized to be associated with patient morbidity and mortality. Research on the relationship between diarrhea and the incidence of transaminitis, severity and mortality has never been carried out, so further research is neededMethod: Descriptive-analytic research design with a case-control study approach. Sampling using consecutive sampling on patients in the inpatient installation of dr. Saiful Anwar, Malang. Research data on diarrhea incidence, transaminitis, severity, and mortality were obtained from secondary data on COVID-19 patients. Data were analyzed using chi-square with a significance level p 0.05Results: The incidence of diarrhea in COVID-19 patients with transaminitis was 45.8% and significantly associated (p = 0.025). Diarrhea in COVID-19 patients was associated with severity (p = 0.046) and patient mortality (p = 0.028).Conclusion: There is a relationship between the incidence of diarrhea in COVID-19 patients with trasnsaminitis, severity and mortality